Native-English speaking teachers' experiences in East-Asian language programs. (February 2020) - Jeon, Mihyon
Abstract: This article examines the experiences of transnational teachers of English in government-funded English language teaching programs, each of which recruits, trains, and administers native speakers of English: Hong Kong's Native-speaking English Teachers scheme (NET), the Japan Exchange and Teaching program (JET), the English Program in Korea (EPIK), and Teach and Learn in Korea (TaLK). It focuses on the relationship between the participation and experiences of native-English speaking teachers and the programs' different policies and institutional structures. The findings demonstrate that these different policies and institutional structures—such as the program aims, eligibility requirements, policies on salary and benefits—have significant implications for the participation of native-English speaking teachers in these programs. This research, with its focus on the experiences of these teachers, extends our understanding of their involvement in English language teaching in Asia. It urges us to locate transnationalism and the global spread of English within a much more complex field of social power relations, calling for more insightful approaches to English language teaching.